Daily Commute of Circular Migrant in Greater Jakarta: a Review: A REVIEW - Hidayati, Inayah (LPPM UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
This research aims to explain the motive of the circular migrant worker in Greater Jakarta. As a destination city, Jakarta is an area with a relatively close distance to the Greater Jakarta area, and there are many choices of transportation. The circular migrant has an exceptional condition: they only move to work or education but do not settle in the destination. The study uses descriptive methods to understand the phenomenon of circular mobility to Jakarta. The data collected from the publication of Statistic Indonesia and in-depth interviews. The results showed that the majority of commuters to Jakarta came from Depok City and Bekasi City. The motives of commuters are for work (83 per cent) and education (17 per cent). The large proportion of commuters with the prior status of work activities shows that economic factors, especially higher income, are still the main reason for commuting. Circular migrant prefers electric railroad line (KRL) because it is relatively fast, cheap and free from traffic jams. The high level of traffic congestion in Jakarta forces commuters to choose the most profitable mode of transportation.